Sharing Oral History With Arctic Indigenous Communities: Ethical Implications of Bringing Back Research Results. (November 2019) - Allemann, Lukas; Dudeck, Stephan
This article discusses ethical implications when sharing results in oral history research. We look at a case study of an Arctic community in Russian Lapland dealing with boarding school experiences. Bringing back research results about this topic provoked diverse reactions. We examine how the social life of stories and the social life of research are interconnected. By questioning the strict applicability of preformulated ethical research principles, we conclude that bringing back research results poses an opportunity to negotiate an appropriate form of reciprocity in research and to gain a deeper understanding of social processes in the communities under study. We identify principles of long-term engagement, collaborative methodologies, and inclusion into the cultural intimacy of the participating community as preconditions for a robust ground for ethics in oral history research.